2014
DOI: 10.1017/s0954579414000649
|View full text |Cite
|
Sign up to set email alerts
|

Social stress and the oxytocin receptor gene interact to predict antisocial behavior in an at-risk cohort

Abstract: Polymorphisms in the oxytocin receptor gene (OXTR) are commonly associated with prosocial behaviors in the extant literature, yet their role in antisocial behaviors has rarely been explored, particularly during the transition from adolescence to early adulthood. We examined a prospective cohort (N=404), collecting youth, mother and clinician reports of conduct disordered and antisocial behavior at age 15 and 20. The oxytocin receptor rs53576 polymorphism was hypothesized to interact with social stress to predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 50 publications
2
36
0
1
Order By: Relevance
“…Among G allele carriers this association was mediated by subjective ratings of interpersonal distrust. Support for this higher sensitivity to a dysfunctional or stressful social environment in rs53576 G allele carriers was further substantiated by both observational (Burkhouse et al, 2015; Dannlowski et al, 2015; Hostinar et al, 2014; Smearman et al, 2015; Sturge-Apple et al, 2012; Windle and Mrug, 2015) and experimental studies (Chen et al, 2011; McQuaid et al, 2015; Norman et al, 2012). As examples of observational studies, it could be shown that rs53576 GG homozygous subjects with ELS exposure have a smaller bilateral volume of the ventral striatum, a key structure of the dopaminergic nigrostriatal pathway (Dannlowski et al, 2015) which is implicated in both depression risk (Nestler and Carlezon, 2006) and parenting behavior (Strathearn et al, 2009).…”
Section: Gene-environment Interactions and Epigenetic Modificationmentioning
confidence: 89%
“…Among G allele carriers this association was mediated by subjective ratings of interpersonal distrust. Support for this higher sensitivity to a dysfunctional or stressful social environment in rs53576 G allele carriers was further substantiated by both observational (Burkhouse et al, 2015; Dannlowski et al, 2015; Hostinar et al, 2014; Smearman et al, 2015; Sturge-Apple et al, 2012; Windle and Mrug, 2015) and experimental studies (Chen et al, 2011; McQuaid et al, 2015; Norman et al, 2012). As examples of observational studies, it could be shown that rs53576 GG homozygous subjects with ELS exposure have a smaller bilateral volume of the ventral striatum, a key structure of the dopaminergic nigrostriatal pathway (Dannlowski et al, 2015) which is implicated in both depression risk (Nestler and Carlezon, 2006) and parenting behavior (Strathearn et al, 2009).…”
Section: Gene-environment Interactions and Epigenetic Modificationmentioning
confidence: 89%
“…For instance, Sturge-Apple et al (2012) found evidence for increased susceptibility to interparental conflict on parental sensitivity among mothers with the GG genotype on OXTR rs53576. Similarly, G allele carriers had higher levels of antisocial behavior in the context of high social stress (Smearman et al, 2014), were more at risk for depressive symptoms when they had experienced high early adversity (McQuaid et al, 2013), and were more responsive to the effects of oxytocin inhalation (Marsh et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Lower oxytocin concentrations have also been observed in the CSF 162 and plasma 163 of women with a history of childhood abuse and borderline personality disorder. Interestingly, although a particular variation in the gene encoding the oxytocin receptor is generally associated with increased prosocial behavior, when it interacts with developmental stress it is associated with increased levels of antisocial behaviors 164 .…”
Section: Oxytocin and Vasopressinmentioning
confidence: 99%